Ozone Treatment Improved the Resistive Switching Uniformity of HfAlO2 Based RRAM Devices - Lifeng Liu; Yi Hou; Weibing Zhang; Dedong Han; Yi Wang (Advances in Condensed Matter Physics)
HfAlO2 based resistive random access memory (RRAM) devices were fabricated using atomic layer deposition by modulating deposition cycles for HfO2 and Al2O3. Effect of ozone treatment on the resistive switching uniformity of HfAlO2 based RRAM devices was investigated. Compared to the as-fabricated devices, the resistive switching uniformity of HfAlO2 based RRAM devices with the ozone treatment is significantly improved. The uniformity improvement of HfAlO2 based RRAM devices is related to changes in compositional and structural properties of the HfAlO2 resistive switching film with the ozone treatment.